2018
DOI: 10.4322/acr.2018.039
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosarcomatous dermatofibrosarcoma protuberans from scar following trauma

Abstract: Dermatofibrosarcoma protuberans (DFSP) is an uncommon soft tissue neoplasm of low metastatic potential notable for its progressive growth and high rate of local recurrence after surgical excision. Fibrosarcomatous transformation of DFSP (FS-DFSP) is a rare variant characterized by higher rates of local recurrence and metastasis. Trauma has been hypothesized as a potential risk factor for the development of DFSP, although clear evidence has been lacking. In this study, we report a case of FS-DFSP that was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Some suggested that trauma could serve as a trigger in stimulating the neoplasm development in a person predisposed by a desmoplastic diathesis 20 . Moreover, others insisted that trauma could play an important etiological role 3,7 . Constant irritation, infection, chronic ulceration, the release of toxins from the injury, poor lymphatic regeneration or exposure to harmful environmental agents may lead to the malignant degeneration in chronic burn scars 11,21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some suggested that trauma could serve as a trigger in stimulating the neoplasm development in a person predisposed by a desmoplastic diathesis 20 . Moreover, others insisted that trauma could play an important etiological role 3,7 . Constant irritation, infection, chronic ulceration, the release of toxins from the injury, poor lymphatic regeneration or exposure to harmful environmental agents may lead to the malignant degeneration in chronic burn scars 11,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, others insisted that trauma could play an important etiological role. 3,7 Constant irritation, infection, chronic ulceration, the release of toxins from the injury, poor lymphatic regeneration or exposure to harmful environmental agents may lead to the malignant degeneration in chronic burn scars. 11,21,22 DFSPs developed at the various injection or insertion sites have been reported (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 Local trauma has been described as a potential risk factor for tumor onset. 2 The most common sites of involvement are the trunk (40%–50%), the proximal limbs (30%–40%), and the head and cervical region (10%–15%). In the literature review, 11 reports of tumors located in the plantar region were retrieved.…”
Section: Introductionmentioning
confidence: 99%